miR-29c improves skeletal muscle mass and function throughout myocyte proliferation and differentiation and by repressing atrophy-related genes - Silva, William José; Graça, Flavia Aparecida; Cruz, André; Silvestre, João Guilherme; Labeit, Siegfried; Miyabara, Elen Haruka; Yan, Chao Yun Irene; Wang, Da Zhi; Moriscot, Anselmo Sigari (Acta physiologica, 2019)
Aim To identify microRNAs (miRs) involved in the regulation of skeletal muscle mass. For that purpose, we have initially utilized an in silico analysis, resulting in the identification of miR-29c as a positive regulator of muscle mass. Methods miR-29c was electrotransferred to the tibialis anterior to address its morphometric and functional properties and to determine the level of satellite cell proliferation and differentiation. qPCR was used to investigate the effect of miR-29c overexpression on trophicity-related genes. C2C12 cells were used to determine the impact of miR-29c on myogenesis and a luciferase reporter assay was used to evaluate the ability of miR-29c to bind to the MuRF1 3′UTR. Results The overexpression of miR-29c in the tibialis anterior increased muscle mass by 40%, with a corresponding increase in fibre cross-sectional area and force and a 30% increase in length. In addition, satellite cell proliferation and differentiation were increased. In C2C12 cells, miR-29c oligonucleotides caused increased levels of differentiation, as evidenced by an increase in eMHC immunostaining and the myotube fusion index. Accordingly, the mRNA levels of myogenic markers were also increased. Mechanistically, the overexpression of miR-29c inhibited the expression of the muscle atrophic factors MuRF1, Atrogin-1 and HDAC4. For the key atrogene MuRF1, we found that miR-29c can bind to its 3′UTR to mediate repression. Conclusions The results herein suggest that miR-29c can improve skeletal muscle size and function by stimulating satellite cell proliferation and repressing atrophy-related genes. Taken together, our results indicate that miR-29c might be useful as a future therapeutic device in diseases involving decreased skeletal muscle mass.